3D-scanning and 3D-printing of Paralympic alpine skiing sit-skiing seats - Goll, M.; Frühschütz, H.; Trautner, L.; Wörgötter, E.; Junior, V.; Osing, L. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: According to Burkett (2012): "[...] connectivity is critical to the effective operation of the assistive device" for athletes in Paralympic winter sports. Further, the author concludes, "[...] the key issue is matching the residual function of the person with the assistive equipment". In sit-skiing, the connection between athlete and the assistive device (sit-ski) is a seat shell. Material fatigue of the seat led to the necessity of an exact replication. Three replication attempts were performed using the standard procedure of thermoforming. However, according to the athlete, the results did not deliver a seat with the same response characteristics; also, the handling performance compared to the original seat was not satisfactory. The aim of this proof of concept was to deliver an exact replication of the original seat by implementing a digital process chain of 3D-scanning and 3D-printing. After a successful seat replication, the next step was to customize a new seat based on the athlete`s body form using the same digital technology and process chain. Here, body shape 3D-data were obtained from scanning the athlete`s vacuum imprint in a sitting position on the sit-ski frame.